IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PUSAT RESTORASI DAN PEMBELAJARAN MANGROVE MENGARE (Universitas Negeri Surabaya, 2023)
Mangrove Restoration and Learning Center (PRPM) located in Tanjung Widoro Village, Bungah Subdistrict, GresikRegency is one of the outputs of the Community Development Corporate Social Responsibility (CSR) program of PTPetrokimia Gresik which aims to conserve mangroves, reduce the impact of abrasion, and empower coastal communities. Thepurpose of this study is to determine the implementation of the PRPM CSR program with a review of the Triple Bottom Line(TBL) and Community Development aspects. The research type is descriptive qualitative with a constructivist paradigm andcase study research method to facilitate the construction of social reality based on how and why events occur. Data collectionwas conducted using semi-structured interviews, passive participatory observation, and documentation of past events. Datavalidation was done by triangulating techniques and sources, while data analysis used the Miles & Huberman interactiveanalysis model. The results of this study show that PRPM CSR is implemented in stages consisting of planning, activityimplementation, evaluation, and reporting. Community Development and Triple Bottom Line (TBL) aspects have beenimplemented well although there are some parts that must be improved. This research is expected to be a literacy and referencematerial related to the knowledge of the implementation of CSR and Community Development programs.